2022
DOI: 10.53444/deubefd.1082616
|View full text |Cite
|
Sign up to set email alerts
|

Müzik Öğretmeni Adaylarının 2006 ve 2018 Lisans Programlarında Bulunan Piyano Derslerine Yönelik Tutum ve Görüşlerinin İncelenmesi

Abstract: Bu çalışmanın amacı, 2018 yılında uygulamaya konan müzik öğretmenliği lisans programının piyano eğitimi açısından öğrenciler üzerindeki etkilerinin, öğrencilerin derse yönelik tutum ve görüşleri doğrultusunda belirlenmesidir. Bu amaçla öğrencilere öncelikle “Piyano Dersine Yönelik Tutum Ölçeği” (Tufan ve Güdek, 2008) uygulanmıştır. Öğrencilerin piyano dersine yönelik tutumlarının cinsiyet, sınıf düzeyi, mezun oldukları lise türü ve dahil oldukları lisans programı değişkenlerine göre farklılık gösterip gösterme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…This situation, according to expert opinions, caused students to be unable to prepare a sufficient basis for other lessons and their teacher competencies were incomplete. Şahin and Güven (2022), in their study measuring the attitudes of individuals who received piano education in 2006 and 2018 music education undergraduate programs, concluded that the attitudes of students who received education in the 2018 program were negative and found themselves inadequate. Atalay and Kumtepe (2022) Atalay and Kumtepe (2022) emphasized the importance of the hearing education course in terms of including psychomotor goals, thanks to applied goals such as being able to hear intervals, reading solfege and writing musical dictation along with cognitive goals.…”
Section: Discussionmentioning
confidence: 99%
“…This situation, according to expert opinions, caused students to be unable to prepare a sufficient basis for other lessons and their teacher competencies were incomplete. Şahin and Güven (2022), in their study measuring the attitudes of individuals who received piano education in 2006 and 2018 music education undergraduate programs, concluded that the attitudes of students who received education in the 2018 program were negative and found themselves inadequate. Atalay and Kumtepe (2022) Atalay and Kumtepe (2022) emphasized the importance of the hearing education course in terms of including psychomotor goals, thanks to applied goals such as being able to hear intervals, reading solfege and writing musical dictation along with cognitive goals.…”
Section: Discussionmentioning
confidence: 99%